Amphibia, Anura, Centrolenidae, Hyalinobatrachium carlesvilai Castroviejo-Fisher, Padial, Chaparro, Aguayo and de la Riva, 2009: First country record, Brazil - Cisneros-Heredia, Diego F.; Strüssmann, Christine; Ávila, Robson W. [UNESP]; Kawashita-Ribeiro, Ricardo A. (My University, 2010)
We present the first Brazilian record of the recently-described glassfrog Hyalinobatrachium carlesvilai Castroviejo-Fisher, Padial, Chaparro, Aguayo and de la Riva, 2009. This species, previously known in Peru and Bolivia, was collected at two localities at the municipality of Aripuanã, northern state of Mato Grosso, Brazil. © 2010 Check List and Authors.
Keywords: Amphibia; Anura; Centrolenidae; Curatella americana; Hyalinobatrachium